2016
DOI: 10.1016/j.patrec.2015.08.028
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of nano-scale carbon structure by HRTEM and lattice fringe analysis

Abstract: An image analysis algorithm is applied to materialsfor characterization of solid-state structure on a nanometer scale using model carbon materials. Nanoscale carbons in the form of "soots" offer ease of demonstration while being relevant to human health and climate concerns. Demonstrated here is an image analysis algorithm applied to three nanoscaled carbon materials: a disordered soot, and two highly ordered soots featuring flat or curved atomic layer planes. Nanostructure parameters consisting of graphene la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 49 publications
1
14
0
Order By: Relevance
“…Interestingly, at the particle core the tortuosity of the fringes decreases and their degree of stacking increases. This could be due to thermally-driven graphitisation given the high temperatures and the possible lack of internal oxidation [13,56].…”
Section: Evolution Of the Internal Structure Of Primary Particles In mentioning
confidence: 99%
“…Interestingly, at the particle core the tortuosity of the fringes decreases and their degree of stacking increases. This could be due to thermally-driven graphitisation given the high temperatures and the possible lack of internal oxidation [13,56].…”
Section: Evolution Of the Internal Structure Of Primary Particles In mentioning
confidence: 99%
“…Soot nanostructure is related to particle formation history in the combustion chamber [14] and its dependent of the initial fuel [15]. Also, soot surface chemistry, which it is linked to soot's environmental and health impact, is dependent on its nanostructure [16,17]. Furthermore, soot reactivity, defined as the ease to oxidise mature soot [9], depends on its physicochemical properties.…”
Section: Introductionmentioning
confidence: 99%
“…The morphology, nanostructure, chemical functional groups and ash content has been reported to impact the soot oxidation characteristics [8,9,15,16,18,19], although there is no clear agreement about the contribution of each property [18]. In diesel engines, it is thought that soot properties can be altered, in order to produce a more reactive soot resulting in less demanding regeneration events in diesel particulate filters [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that the fringe length and tortuosity obtained from HRTEM images could change with a long exposure time of the electron beam irradiation [70]. Here this effect of the electron beam was ignored due to the short exposure time.…”
Section: Analysis Methodsmentioning
confidence: 99%